Systematic Review and Meta-Analysis of Tacrolimus versus Ciclosporin as Primary Immunosuppression After Liver Transplant. - Gorden Muduma; Rhodri Saunders; Isaac Odeyemi; Richard F Pollock (PLoS ONE)
Background and aims Several meta-analyses comparing ciclosporin with tacrolimus have been conducted since the 1994 publication of the tacrolimus registration trials, but most captured data from randomized controlled trials (RCTs) predating recent improvements in waiting list prioritization, induction protocols and concomitant medications. The present study comprised a systematic review and meta-analysis of ciclosporin and tacrolimus in liver transplant recipients using studies published since January 2000. Methods Searches of PubMed, the Cochrane Library and EMBASE identified RCTs of tacrolimus and ciclosporin as the immunosuppressant in adult primary liver transplant recipients, published between January 2000 and August 6, 2014. A random effects meta-analysis was conducted to evaluate the relative risk of death, graft loss, acute rejection (AR), new-onset diabetes after transplantation (NODAT) and hypertension with tacrolimus relative to ciclosporin at 12 months. Results The literature search identified 11 RCTs comparing ciclosporin with tacrolimus. Relative to ciclosporin, tacrolimus was associated with significantly improved outcomes in terms of patient mortality (risk ratio [RR] with ciclosporin of 1.26; 95% confidence interval [95%CI] 1.01-1.58). Tacrolimus was superior to ciclosporin in terms of hypertension (RR with ciclosporin 1.26; 95%CI 1.07-1.47), but inferior in terms of NODAT (RR with ciclosporin 0.60; 95%CI 0.47-0.77). There were no significant differences between ciclosporin and tacrolimus in terms of graft loss or AR. Conclusions Meta-analysis of RCTs published since 2000 showed tacrolimus to be superior to ciclosporin in terms of patient mortality and hypertension, while ciclosporin was superior in terms of NODAT. No significant differences were identified in terms of graft loss or AR. These findings provide further evidence supporting the use of tacrolimus as the cornerstone of immunosuppressive therapy in liver transplant recipients.